2010
DOI: 10.15283/ijsc.2010.3.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutritional Supplements on Muscle-Derived Stem Cells in vitro

Abstract: Postnatal muscle stem cells, recognized as myogenic satellite cells, were isolated from sheep skeletal muscle and used in these experiments. Forty-one different metabolic compounds that are commonly found in commercially-available oral supplements were exposed to primary muscle stem cell cultures, in an effort to ascertain whether any one compound could alter satellite cell proliferation or differentiation (a first step towards elucidating the metabolomics or nutrigenomics of these stem cells). These compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…A similar cell proliferation pattern was reported by Vishnyakova et al [ 26 ], with a gradual increase of human skin fibroblast proliferation with increasing carnosine concentrations (up to 15 mM) and a return to proliferation values similar to the 0 mM treatment at 30 mM carnosine. Previous studies have reported an increase of human myoblasts proliferation when 20 mM carnosine was added to the culture medium after 30 days of cell growth [ 17 ], whereas there was no effect of carnosine on sheep myoblasts proliferation [ 27 ]. However, in the latter study, the carnosine concentrations used were very low, which may account for the lack of effect.…”
Section: Resultsmentioning
confidence: 99%
“…A similar cell proliferation pattern was reported by Vishnyakova et al [ 26 ], with a gradual increase of human skin fibroblast proliferation with increasing carnosine concentrations (up to 15 mM) and a return to proliferation values similar to the 0 mM treatment at 30 mM carnosine. Previous studies have reported an increase of human myoblasts proliferation when 20 mM carnosine was added to the culture medium after 30 days of cell growth [ 17 ], whereas there was no effect of carnosine on sheep myoblasts proliferation [ 27 ]. However, in the latter study, the carnosine concentrations used were very low, which may account for the lack of effect.…”
Section: Resultsmentioning
confidence: 99%
“…Untrained men consumed .5 g/kg/body mass/day (~ 4 g) for 21 days before the eccentric protocol [ 21 ] (Table 2 ). Healthy, active volunteers (male and female) consumed mixed low-to-moderate doses of taurine at multiple time periods.…”
Section: Dosage Resultsmentioning
confidence: 99%
“…Although taurine is not a BCAA, taurine could possibly delay muscle soreness by improving satellite cell activation and recovery after a single bout of high intensity, muscle-damaging exercise [ 10 , 78 , 79 , 83 ]. Satellite cells are responsible for myofiber development, proliferation, differentiation, and renewal [ 10 , 21 ]. Since taurine is found in high concentration in the skeletal muscle, after a high bout of exercise or injury, the myofibers are damaged resulting in disruption of the sarcolemma which causes the activation of satellite cells and release of taurine [ 2 , 5 , 10 , 25 , 66 , 80 , 86 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that serum lot to lot variations can profoundly alter satellite cell proliferation [41], so it is important to pre-test different lots to obtain optimal growth. To avoid the costs and variability associated with serum, several serum-free media have been developed specifically for enhancing satellite cell proliferation and differentiation [68]. In a similar manner, addition of soluble growth factors is essential for recreating in vivo myogenesis and maximizing proliferation of isolated satellite cells.…”
Section: Proliferation and Induction In Vitromentioning
confidence: 99%